The brothers Bulger: how they terrorized and corrupted Boston for a quarter century - Carr, Howie (Warner Books, 2006)
"A portrait of Boston's infamous Bulger brothers, Whitey and Billy--one as the city's most feared mobster, the other as a power in the Massachusetts State Senate."--Provided by publisher.